2016
DOI: 10.7150/thno.14960
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Particle Accumulation, Chemosensitivity and Thermosensitivity for Effective Solid Tumor Therapy Using Thermosensitive Liposomes and Hyperthermia

Abstract: Doxorubicin (Dox) loaded thermosensitive liposomes (TSLs) have shown promising results for hyperthermia-induced local drug delivery to solid tumors. Typically, the tumor is heated to hyperthermic temperatures (41-42 °C), which induced intravascular drug release from TSLs within the tumor tissue leading to high local drug concentrations (1-step delivery protocol). Next to providing a trigger for drug release, hyperthermia (HT) has been shown to be cytotoxic to tumor tissue, to enhance chemosensitivity and to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…For all groups, an increasing liposomal uptake in tumors was observed over time due to the "enhanced permeability and retention (EPR) effect" intrinsic to most tumor tissues (44,45). It is previously reported that hyperthermia can increase the EPRdriven uptake of liposomes in the tumor (41,(46)(47)(48), which could lead to additional dox uptake from residual nonreleased TSLs over time. However, this increase in EPR effect can be tumor-dependent (46) and for the R1 rhabdomyosarcomas studied here, no HIFU-induced increase in EPR effect was observed as all groups showed comparable TSL uptake 48 h after injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all groups, an increasing liposomal uptake in tumors was observed over time due to the "enhanced permeability and retention (EPR) effect" intrinsic to most tumor tissues (44,45). It is previously reported that hyperthermia can increase the EPRdriven uptake of liposomes in the tumor (41,(46)(47)(48), which could lead to additional dox uptake from residual nonreleased TSLs over time. However, this increase in EPR effect can be tumor-dependent (46) and for the R1 rhabdomyosarcomas studied here, no HIFU-induced increase in EPR effect was observed as all groups showed comparable TSL uptake 48 h after injection.…”
Section: Discussionmentioning
confidence: 99%
“…It is previously reported that hyperthermia can increase the EPRdriven uptake of liposomes in the tumor (41,(46)(47)(48), which could lead to additional dox uptake from residual nonreleased TSLs over time. However, this increase in EPR effect can be tumor-dependent (46) and for the R1 rhabdomyosarcomas studied here, no HIFU-induced increase in EPR effect was observed as all groups showed comparable TSL uptake 48 h after injection. For both hyperthermia-treated animals and animals that did not receive HIFU treatment, SPECT imaging showed a relatively homogeneous uptake across the tumor, with a trend of increasing TSL concentration over 48 h. Although uptake of TSLs is a slow process with typical maximum tumor concentration reached after 8-48 h (46), the therapeutically relevant process is the intravascular release of dox from TSLs, which takes place while hyperthermia is applied, that is, within the first 40 min after injection of TSLs.…”
Section: Discussionmentioning
confidence: 99%
“…showing that the two stage HT treatment protocol has substantial advantages [63]. In our study presented here we apply the repeated FUS protocols sequentially post injection.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…10 Among the various types of combination therapies, combined hyperthermia and chemotherapy could trigger drug release from drug carriers inside cells, enhance drug uptake by cells, or enhance antitumor efficacy via a synergistic effect. 4,11 Recently, "nanotheranostics" has attracted much attention due to the development of nanomaterials with integrated diagnostic and therapeutic functions. [12][13][14][15][16] These nanomaterials can simultaneously serve as multifunctional contrast agents, such as for magnetic resonance (MR), ultrasound (US) or uorescence imaging of tumors and drug delivery or ablation of tumors.…”
Section: Introductionmentioning
confidence: 99%